Spiritual vulnerability through demonization in curses? A critical reassessment - Cheong Weng Kit (Jurnal Teologi Amreta (ISSN: 2599-3100))
This paper examines the Pentecostal/charismatic concerns of spiritual vulnerability of Christians through demonisation in curses. It will studies popular writers such as Derek Prince and Rebecca Brown and academic authors such as Charles Kraft and Ed Murphy to assess the accuracy of such views in comparison to the biblical data on curse to propose a more robust and sound theological, ministerial and misssiological understanding and praxis for how Christians may engage with curses.